2021
DOI: 10.1002/jha2.188
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for acute pain in sickle cell disease: A randomized double‐blinded placebo‐controlled phase II clinical trial

Abstract: Pain in sickle cell disease (SCD) can have a neuropathic component. This randomized phase II double‐blinded placebo‐controlled study evaluated the efficacy of gabapentin in reducing pain and opioid consumption (morphine‐equivalent dose [MED]) during acute vaso‐occlusive crisis (VOC). Of 90 patients aged 1–18 years with VOC pain, 45 were randomized to a single gabapentin dose (15 mg/kg) and 45 to placebo, in addition to standard treatment; 42 and 44 patients were evaluable in the gabapentin and placebo arms, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…One small randomized controlled trial in adults with SCD compared pregabalin to placebo for impact on self-reported NP and quality of life, but limitations of small sample size, attrition, and short duration of the study limit meaningful conclusions [24,26]. In children with SCD, one trial randomized patients presenting with acute vaso-occlusive pain to gabapentin or placebo but did not include NP as a prerequisite for study inclusion or as a specific outcome measure [27]. However, case reports and anecdotal experience suggest that these interventions may alleviate some of the symptoms stemming from SCD-related NP in children and adolescents [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…One small randomized controlled trial in adults with SCD compared pregabalin to placebo for impact on self-reported NP and quality of life, but limitations of small sample size, attrition, and short duration of the study limit meaningful conclusions [24,26]. In children with SCD, one trial randomized patients presenting with acute vaso-occlusive pain to gabapentin or placebo but did not include NP as a prerequisite for study inclusion or as a specific outcome measure [27]. However, case reports and anecdotal experience suggest that these interventions may alleviate some of the symptoms stemming from SCD-related NP in children and adolescents [28,29].…”
Section: Introductionmentioning
confidence: 99%